2009
DOI: 10.1371/journal.pone.0006152
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Regulation of HIC (Human I-mfa Domain Containing Protein) Expression

Abstract: Human I-mfa domain containing protein (HIC) differentially regulates transcription from viral promoters. HIC affects the Wnt pathway, the JNK/SAPK pathway and the activity of positive transcription elongation factor-b (P-TEFb). Studies exploring HIC function in mammalian cells used ectopically expressed HIC due to undetected endogenous HIC protein. HIC mRNA contains exceptionally long 5′ and 3′ untranslated regions (UTRs) compared to the average length of mRNA UTRs. Here we show that HIC protein is subject to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Earlier studies have demonstrated that I-mfa plays an important role in the inhibition of myogenesis (8), skeletogenesis (25,53), and osteoclastogenesis (37). I-mfa may also function as a tumor suppressor gene (27,28,43). The present study provided evidence, for the first time, that I-mfa is also present and functional in kidney cells.…”
Section: Discussionsupporting
confidence: 74%
“…Earlier studies have demonstrated that I-mfa plays an important role in the inhibition of myogenesis (8), skeletogenesis (25,53), and osteoclastogenesis (37). I-mfa may also function as a tumor suppressor gene (27,28,43). The present study provided evidence, for the first time, that I-mfa is also present and functional in kidney cells.…”
Section: Discussionsupporting
confidence: 74%
“…Collectively, these observations suggest that HIC acts as a cellular competitor with importin β for binding the Rev NLS, and that the balance between HIC and importin β could influence the rate of Rev nuclear import. Interestingly, we and others have recently described that the expression of HIC is tightly regulated at the transcriptional level [ 37 , 38 ]. Furthermore, compared to 293T where endogenous levels of HIC expression are sufficient to down-modulate HIV-1 Rev activity, HIC is highly expressed in PBMCs and more specifically in HIV-1 target cells, including CD4+ T-cells and monocytes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to investigate the mechanisms by which MDFIC protein is restricted to valve endothelial cells. To further explore the possibility that, as previously reported (37), full-length MDFIC protein is posttranslationally regulated and subject to rapid proteosomal degradation, we ectopically expressed constructs encoding full-length and M131fs* MDFIC in HeLa cells and treated cells with the proteosomal and lysosomal inhibitors MG132 and chloroquine. In contrast to untreated cells, more full-length protein was consistently detected in cells treated with these inhibitors (fig.…”
Section: Mdfic Stability Is Regulated By Foxc2 Gata2 and Nfatc1mentioning
confidence: 98%